Analisis Perbandingan Kinerja Keuangan Sebelum dan Saat Pandemi Covid-19 Pada Kantor Unit Penyelenggara Pelabuhan Kelas II Pemenang Kabupaten Lombok Utara - Suhaeri, Muhammad; Kisnawati, Baiq Kisnawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
The impact of the Covid-19 pandemic has also been felt in the sea transportation sector, especially ports that serve transportation in the tourism sector. The transportation sector is a sector related to development and development in the country's economy. This study aims to determine differences in financial performance before and during the Covid-19 pandemic at the Class II Pemenang Port Operations Unit Office. This study uses Budget Management Performance Indicators (IKPA) which are proxied by the quality aspects of budget planning, the quality aspects of budget execution and the quality aspects of budget implementation results in measuring financial performance. The location of this research was conducted at the Class II Pemenang Port Administration Unit Office. The data collection technique used is documentation with the type of quantitative data obtained secondaryly through the financial reports of the Class II Winner Port Operations Unit Office. Data were analyzed using SPSS 23 with different tests and hypotheses. The results of this study indicate that there are differences in financial performance that are proxied by the quality aspects of budget planning, the quality aspects of budget execution and the quality aspects of the results of budget implementation before and during the Covid-19 pandemic at the Pemenang Class II Port Operations Unit Office.